In vitro susceptibility of Mycobacterium marinum to eight antimicrobial agents. - Sanders, W J (1980)
The in vitro susceptibilities of 16 Mycobacterium marinum strains to eight antimicrobial agents were determined by the agar dilution technique. The most active drugs were amikacin and kanamycin. Tetracycline, doxycycline, and minocycline were inhibitory, predominantly at concentrations slightly below the expected blood and tissue levels. Trimethoprim-sulfamethoxazole and erythromycin demonstrated activity only at concentrations greater than those usually attained in serum and tissues. Gentamicin was relatively inactive.